Sílbale a Willie - Keats, Ezra Jack (New York, N.Y., U.S.A. : Puffin Books, 1996)
Willie longs to be able to whistle for his dog and makes many ingenious attempts.
Willie quiere poder silbarle a su perro y trata de hacerlo de muchas maneras ingeniosas.
Translation of: Whistle for Willie.
Reprint. Originally published: New York : Viking, 1992.
560
Accelerated Reader AR
Keywords: African Americans -- Juvenile fiction; Dogs -- Juvenile fiction; Whistling -- Juvenile fiction; Afronorteamericanos -- Novela juvenil; Perros -- Novela juvenil; Silbido -- Novela juvenil